4CPS-133 Response to vemurafenib-cobimetinib with reduced doses in a patient with metastasic melanoma: concerning a case - Santana, E Ramos (Eur J Hosp Pharm, 2018)
BACKGROUND: Melanoma is the cutaneous tumour with the highest mortality. BRAF inhibitors are indicated for patients with metastatic melanoma and are part of the first-line treatment of this disease. PURPOSE: To describe the clinical course of a patient diagnosed with metastatic melanoma who developed a severe toxicity to the treatment with vemurafenib-cobimetinib and required dose reduction. MATERIAL AND METHODS: Patient’s medical history and drug dispensing records were reviewed through Drago AE(®) and FarmaTools(®). RESULTS: A 64-year-old female patient diagnosed with metastatic malignant melanoma. V600E mutation was confirmed as well as in HMB 45 and S100. A combined scan of positron emission tomography (PET) and computed tomography (CT) scan were performed. The study shows malignant tumoural disease at the lymph node, pulmonary, hepatic, bone, multiple tumour implants in subcutaneous and muscular cellular tissue, abdominal implants and probable cerebral metastatic injury. Treatment with the vemurafenib 960 mg (2–0–2) and cobimetinib 60 mg (0–0–3) was started. After the first cycle, the patient developed a severe dermal toxicity (grade III). Following resolution, it was decided to continue the treatment with reduced doses: Vemurafenib 720 mg (1–0–2) and cobimetinib 40 mg (0–0–2). Two months’ later, an MRI of the skull is performed, with a marked decrease in brain injury, but a post-treatment toxic leukopathy is evident, accompanied by gastrointestinal toxicity with asthaenia, nausea and hyporexia, reducing the dose of vemurafenib to 480 mg (1–0–1) and cobimetinib to 20 mg (0–0–1). One month later, a new decrease was observed, compared to the previous study. The rest of the lesions described in the first PET-CT study do not show significant metabolic activity at present. In view of the good response to treatment, a full dose of the drugs is attempted again, but the dose-dependent dermal toxicity is re-confirmed. Therefore, to date, the patient remains in stable disease with reduced doses of treatment: vemurafenib 720 mg (1–0–2) and cobimetinib 20 mg (0–0–1). CONCLUSION: With the present case we wanted to increase the published evidence on the management of drugs known as ‘targeted therapies’ in metastatic melanoma, showing the case of a dose-dependent dermal toxicity, in which it has been possible to control the evolution of the disease with reduced doses of vemurafenib and cobimetinib. REFERENCES AND/OR ACKNOWLEDGEMENTS: Electronical health record Drago-AE. No conflict of interest